2021
DOI: 10.21608/ejchem.2021.94656.4464
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutathione-S-Transferase M1 (GSTM1) and T1 (GSTT1) Genes on Aluminum Concentration and Oxidative Markers among Autistic Children

Abstract: Autism Spectrum Disorder (ASD) is considered a multifaceted neurodevelopmental disorder. The last two decades showed an increase in its prevalence until reached about 1 in 54 children. Autistic symptoms may be exacerbated when the interaction of the genetic and the environmental risk factors occur, suggesting that gene-environment interaction could be a mechanism underlying the aetiology of ASD. Aluminium is a known neurotoxic metal that has known health effects in humans. Glutathione-S-transferase (GST) genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Moreover, several findings suggested that the differential susceptibility to heavy metals can be explained by the polymorphisms of GST genes, for instance, null alleles of GSTT1 and GSTM1 were associated with a deficiency of enzymatic activity which was related to decreased detoxification and increased oxidative stress [ 43 , 47 ]. According to a recent study in Egypt, children with null GSTM1 and GSTT1 genotypes had a significantly lower level of GST activity compared to other combinations of genotypes, suggesting a poor aluminum detoxification ability [ 48 ]. All of these reports indicate that genetic variation can provide an explanation for differences in Al concentrations in a population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several findings suggested that the differential susceptibility to heavy metals can be explained by the polymorphisms of GST genes, for instance, null alleles of GSTT1 and GSTM1 were associated with a deficiency of enzymatic activity which was related to decreased detoxification and increased oxidative stress [ 43 , 47 ]. According to a recent study in Egypt, children with null GSTM1 and GSTT1 genotypes had a significantly lower level of GST activity compared to other combinations of genotypes, suggesting a poor aluminum detoxification ability [ 48 ]. All of these reports indicate that genetic variation can provide an explanation for differences in Al concentrations in a population.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that Glutathione S-Transferases (GSTs) enzymes have a very essential function in antioxidant protection mechanisms via performing the detoxification of xenobiotics and inactivation of endogenous oxidative stress products [13]. In addition to, our recent study observed that autistic children have reduced glutathione activity, and increased oxidative stress [9]. This open the possibility for novel treatments aiming at planning dietary antioxidant interventions in children with ASD.…”
Section: Introductionmentioning
confidence: 81%
“…7 (2022) recommended via 49% of physicians as a supplementation for children with autism [6]. Some studies have depicted the role of Al in autism spectrum disorder [7][8][9], due to its poor detoxification. The oxidative stress become worse and it is found to be associated with autism severity that significantly lead to ASD progression [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations